The method of moments for electromagnetic scattering analysis accelerated by the polynomial chaos expansion in infinite domains - Yuan, Xiaohui; Ma, Yujing; Huang, Yajun; Huo, Ruijin; Wang, Zhongwang (Frontiers in Physics, 2023)
An efficient method of moments (MoM) based on polynomial chaos expansion (PCE) is applied to fast calculate the electromagnetic scattering problems. The triangle basic functions are used to discretize the surface integral equations. The polynomial chaos expansion is utilized to accelerate the MoM by constructing the surrogate model for univariate and bivariate analysis. The mathematical expressions of the surrogate model for the radar cross section (RCS) are established by considering uncertain parameters such as bistatic angle, incident frequency, and dielectric constant. By using a scattering cylinder example with analytical solution, it is verified that MoM accelerated by PCE presents a considerable advantage in computational expense and speed.